Economics in the shadows of Darwin and Marx : essays on institutional and evolutionary themes - Hodgson, Geoffrey Martin, 1946- (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
"Economics in the Shadows of Darwin and Marx" examines the legacies of these two giants of thought for the social sciences in the twenty-first century.
This collection of essays establishes the importance of Darwinism for economics and other social sciences, and compares the Darwinian legacy with that of Marx.
&#x000A
Introduction -- Marxism, Darwinism, institutionalism -- Darwin and Marx at the crossroads -- Social Darwinism in anglophone academic journals -- Institutionalism versus Marxism : a debate with Alex Callinicos -- Three essays on critical realism -- The uncritical political affinities of critical realism -- Contestable claims by for critical realism in economics -- The problem of formalism in economics -- Habits and individuals; routines and institutions -- What are institutions? -- The hidden persuaders -- The complex evolution of a simple traffic convention -- The nature and replication of routines.
Includes bibliographical references (p. 216-253) and index.
oif 03/01/15
Loan
Keywords: Evolutionary economics; Institutional economics; Social Darwinism; Marxian economics